Environmental Conservation Value of Various Wall Decorations at the Islamic Relics of Sunan Drajat's Tomb - Rikhma Fikriana Farrakin; Ahmad Fauzan Hidayatullah (Universitas Muhammadiyah Magelang, 2023)
The Sunan Drajat Complex stands out as a location adorned with aesthetic decorations, unique to the island of Java. Revered as a wise figure in society, Sunan Drajat has seamlessly integrated into modern life, imparting teachings through art, notably the Sufism teachings of Catur Piwulang. This research aims to identify the principles of environmental conservation values reflected in the wall decorations of Sunan Drajat's tomb in Lamongan. Employing a descriptive qualitative approach, the study draws on the environmental preservation concept of Catur Piwulang, specifically